DEVELOPMENT OF SMART STUDENT LEARNING MEDIA IN IMPROVING STUDENT ABILITIES TO THINK CRITICALLY - Famelia Ariza; Misdalina; Marleni (Esteem Journal of English Education Study Programme, 2024)
The low interest that students have in mathematics classes is the driving force behind this research, which aims to increase students' engagement and comprehension of addition and subtraction concepts by employing smart ladder media. The purpose of this study is to use smart ladder media to increase the Hots Thinking Subject's capacity. SD Negeri 83 Palembang, situated on Jl. Pangeran Ratu Jakabaring, RT 29/ RW 08, 15 Ulu, Seberang Ulu I District, Palembang City, South Sumatra, is the location where this research was conducted. This study falls under the category of development research since it aims to identify Valid, Practical, and Potential Effects. 10 students from class II at SD Negeri 83 Palembang participated in this study; ten students took the practical test and twenty-seven students worked on the questionnaire. In this study, tests and questionnaires were used as data collection methods. The investigation yielded 89% of the results with the criterion "Very valid" across all validators. A practicality test, administered at SD Negeri 83 Palembang, yielded a 56% "Quite practical" proportion among the ten students who completed the questionnaires. At SD Negeri 83 Palembang, the possible impact of providing 10 essay test questions received an 82% "Very Effective" rating.